Emotional Intelligence of Elementary School Age Children in Low and High Classes - Anggraini, Isma Ulul; Wahdan Najib Habiby (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Children's emotional intelligence plays an important role in their success at school. The emergence of cases resulting from a low ability to manage emotions, such as violence and bullying, has a negative impact both physically and psychologically. Tthem research aims to determine the level and development of emotional intelligence in elementary school children. The research method used is qualitative with a case study approach. The research was conducted at State Elementary School 02 Tuban Karanganyar, involving students based on class levels, namely low and high class. Data was collected through questionnaires, interviews, and observations. Data validity with data triangulation and techniques. Data analysis uses interactive analysis. The research results show that the characteristics of students' emotional intelligence vary. Low-class emotional intelligence focuses on recognizing one's own and others' emotions, while high-class emotional intelligence focuses on managing emotions, motivating oneself, and building relationships. However, a high-class student experienced delays in emotional intelligence development due to trauma from physical bullying. It is crucial to help children manage emotions healthily and build self-control skills to prevent delays in emotional intelligence development. Developing emotional intelligence from low to high is essential for overall well-being.